(-3)³ ori [(-7)²-10x]=(-3)⁴x , imi rezolvati asta ?
Răspunsuri la întrebare
Răspuns de
0
- 27 · [ 49 - 10x ] = 81x
- [ 49 -10x ] = (81 : 27)x
-49 + 10x = 3x
- 49 = -10x + 3x
-49 = - 7x
x = ( -49 ) : ( -7) = 7
- [ 49 -10x ] = (81 : 27)x
-49 + 10x = 3x
- 49 = -10x + 3x
-49 = - 7x
x = ( -49 ) : ( -7) = 7
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă